Bacterial microbiota composition of fermented fruit and vegetable juices (jiaosu) analyzed by single-molecule, real-time (SMRT) sequencing. Issue 1 (1st January 2018) - Ma, Da; He, Qiuwen; Ding, Jia; Wang, Huiyan; Zhang, Heping; Kwok, Lai-Yu
ABSTRACT: Commercially manufactured 'jiaosu' (fermented fruit and vegetable juices) have gained popularity in Asia recently. Like other fermented products, they have a high microbial diversity and richness. However, no published study has yet described their microbiota composition. Thus, this work aimed to obtain the full-length 16S rRNA profiles of jiaosu using the PacBio single-molecule, real-time sequencing technology. We described the bacterial microbiota of three jiaosu products purchased from Taiwan and Japan. Bacterial sequences from all three samples distributed across seven different phyla, mainly Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. Forty-three genera were identified (e.g. Ochrobactrum, Lactobacillus, Mycobacterium, and Acinetobacter ). Fifty-five species were identified (e.g. Ochrobactrum lupini, Mycobacterium abscessus, Acinetobacter johnsonii, Lactobacillus paracasei, Lactobacillus delbrueckii, and Petrobacter succinatimandens ). No pathogen sequences were identified within the entire dataset. Moreover, only a low proportion of sequences represented common skin microflora and the food hygiene indicator Escherichia / Shigella, suggesting overall acceptable sanitary conditions during the manufacturing process.